An Ecological and Historical Perspective on Agricultural Development in Southeast Asia - Hayami, Yujiro (World Bank, Washington, DC, 2015)
According to Myint's "vent-for-surplus" theory, development of the economies of Indonesia, the Philippines, and Thailand from the nineteenth century on depended on the natural advantage of large tracts of unused "empty land" with low population density and abundant natural resources of the type typically found in Southeast Asia and Africa at the outset of Western colonization. When these economies were integrated into international trade, hitherto unused natural resources (primary commodities the indigenous people had not valued) became the source of economic development, commanding market value because of high import demand in Western economies. The major delta of Chao Phraya River was the resource base of vent-for-surplus development with rice in Thailand; tropical rain forests filled that role in Indonesia and the Philippines with respect to the production of tropical cash crops. This basic difference underlay differences in the distribution of farm size: the unimodal distribution of peasants or family farms in Thailand and the coexistence of peasants and large estate farms or plantations specializing in tropical export crops in Indonesia and the Philippines. Differences in agrarian development were also shaped by different policies toward the elites preemption of unused land. Under Spanish colonialism, the elite preempted unused land in the Philippines wholesale, bifurcating land distribution between non-cultivating landlords and sharecroppers in lowland rice areas, and between plantation owners and wage laborers in upland areas. In Indonesia, the Dutch government granted long-term leases for uncultivated public land to foreign planters, but prevented alienation of cultivated land from native peasants, to avoid social instability. In Thailand, concessions were granted for private canal building, but the independent kingdom preserved the tradition of giving land to anyone who could open and cultivate it. Relatively homogenous land-owning peasants dominated Thailand's rural sector. As frontiers for new cultivation closed, the plantation systems initial advantage (large-scale development of land and infrastructure) began to be outweighed by its need to monitor hired labor. The peasant system, based on family labor needing no supervision, allowed Thailand's share of the world market in tropical cash crops to grow, as Indonesia and the Philippines lost their traditional comparative advantage. Moreover, land reform in the Philippines made land markets inactive, with resulting distortions in resource allocation and serious underinvestment in agriculture.